A Social Context Model of Envy and Social Undermining - Duffy, Michelle K.; Scott, Kristin L.; Shaw, Jason D.; Tepper, Bennett J.; Aquino, Karl (Academy of Management Journal, 2012)
We integrate moral disengagement, social identification, and social norms theories to develop, test, and replicate a model that explains how and when envy is associated with social undermining. In Study 1, a two-wave study of hospital employees, results support the prediction that the mediated effect of envy on social undermining behavior through moral disengagement is stronger when employees have low social identification with coworkers. Study 2, a four-wave, multilevel study of student teams, shows that the indirect effect of envy on social undermining through moral disengagement is stronger in teams with low team identification and high team undermining norms.